Goal setting, conditions of practice, and task performance: A resource allocation perspective. - Kanfer, Ruth; Ackerman, Phillip L.; Murtha, Todd C.; Dugdale, Brad; Nelson, Leissa (Journal of Applied Psychology, 1994)
Hypotheses regarding the influence of goal assignments on performance of a novel, complex task under varying conditions of practice were derived from a cognitive resource allocation model. Goals and type of practice interacted in their effects on two key performance measures. In the massed-practice conditions, trainees assigned specific, difficult goals tended to perform poorer than trainees in the contorl (do your best goal) conditions. In the spaced-practice conditions, goal trainees performed marginally better than control trainees. Self-report measures of goal commitment, and ontak, off-task, and affective thoughts during breaks and task performance provide additional evidence for the independent and interactive effects of goals and practice conditions on motivation and performance